Ruddlesden–Popper Hybrid Lead Bromide Perovskite Nanosheets of Phase Pure n=2: Stabilized Colloids Stored in the Solid State. Issue 52 (10th November 2021) - Cevallos‐Toledo, Rita B.; Rosa‐Pardo, Ignacio; Arenal, Raul; Oestreicher, Víctor; Fickert, Michael; Abellán, Gonzalo; Galian, Raquel E.; Pérez‐Prieto, Julia
Abstract: Ruddlesden‐Popper lead halide perovskite (RP‐LHP) nano‐nanostructures can be regarded as self‐assembled quantum wells or superlattices of 3D perovskites with an intrinsic quantum well thickness of a single or a few ( n =2‐4) lead halide layers; the quantum wells are separated by organic layers. They can be scaled down to a single quantum well dimension. Here, the preparation of highly (photo)chemical and colloidal stable hybrid LHP nanosheets (NSs) of ca. 7.4 μm lateral size and 2.5 nm quantum well height (thereby presenting a deep blue emission at ca. 440 nm), is reported for the first time. The NSs are close‐lying and they even interconnect when deposited on a substrate. Their synthesis is based on the use of the p ‐toluenesulfonic acid/dodecylamine ( p TS/DDA) ligand pair and their (photo)chemical stability and photoluminescence is enhanced by adding EuBr2 nanodots (EuNDs). Strikingly, they can be preserved as a solid and stored for at least one year. The blue emissive colloid can be recovered from the solid as needed by simply dispersing the powder in toluene and then using it to prepare solid films, making them very promising candidates for manufacturing devices. Abstract : Quantum confined nanosheets (NSs) of 3D perovskites with a thickness of two lead halide layers can be prepared by using the dodecylammonium/tosylate ligand pair. The addition of Eu‐nanodots to the colloid prevented the NSs from a structural rearrangement and/or coalescence. Deep blue‐emissive colloids were recovered by simply dispersing it in toluene.